The Changing Role of Debt in Bankruptcy - Dorene Isenberg (Levy Economics Institute of Bard College, 1989)
The changing economic environment of the late 1980s has been dominated by the financial I innovations brought about by the growing demand for credit by U.S. corporations. When looking at this phenomena from a very long perspective of 50 to 60 years as some researchers have done [Taggart, 1985; Ciccolo and Baum, 1985], he rise in leverage on corporations' balance sheets may not create high anxiety. However, incorporating into that picture the episode known as the Great Depression should give one pause and a moment for reflection. It was the Great Depression that followed the prosperous episodes of the 1920s when households' and the financial sector's use of debt pushed up the private sector's debt-equity ratio. When looking at the rise in debt usage from a more localized view as this study has done, the damage that is possible even without a recession is brought into focus. Debt, short term debt, has emerged as a very decisive factor in the study of bankruptcy. In contrast to the previous studies on failure where earnings and profitability dominated as predictors/determinants, this study has provided support for the view that in this time period the rise in short term debt usage may lead to increases in bankruptcy. As the data also very vividly point out, this increase is not isolated to small firms, but increasingly, large firms are joining the ranks of the failed.
Keywords: 330